2001
DOI: 10.1097/00005537-200102000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Parotid Sialendoscopy

Abstract: Objective: To present our initial experience with sialendoscopy of the parotid duct. Study Design: Methods: Diagnostic and interventional sialendoscopy procedures were performed in 79 and 55 cases, respectively. Diagnostic sialendoscopy was used to classify ductal lesions into sialolithiasis, stenosis, sialodochitis, and polyps. Interventional sialendoscopy was used to treat these disorders. The type of endoscope used, the type of sialolithiasis fragmentation and/or extraction device used, the total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
208
2
20

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(236 citation statements)
references
References 24 publications
6
208
2
20
Order By: Relevance
“…The purpose of treatment is to completely remove the stone. Previous studies suggest that the stone diameter should not be more than 5 mm for Stensen duct and 7 mm for Wharton duct if it is to be removed in one piece without fragmentation [11,12]. Sometimes it is possible to remove even larger stones without fragmentation if they have smoothly ellipsoid configuration [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The purpose of treatment is to completely remove the stone. Previous studies suggest that the stone diameter should not be more than 5 mm for Stensen duct and 7 mm for Wharton duct if it is to be removed in one piece without fragmentation [11,12]. Sometimes it is possible to remove even larger stones without fragmentation if they have smoothly ellipsoid configuration [3].…”
Section: Discussionmentioning
confidence: 99%
“…These include external or internal lithotripsy, laser fragmentation or microdrill [15,16]. The success rate for endoscopic sialolithotomy of larger stones without fragmentation was as low as 35 % [4,12]. Furthermore complications like ductal tear or avulsion may occur if these large stones approached endoscopically [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But with improved and more sensitive methods of detection now available, studies have reported up to 40% incidence of parotid stones in cases of sialolithiasis [5]. This also perhaps explains the higher reported incidence of multiple stones (58%) in the affected parotid gland.…”
Section: Discussionmentioning
confidence: 99%